Elementos sinalizadores da dinâmica da revelação divina em Bruno Forte - Silva, José Vergílio da (2012)
This dissertation presents some elements of the dynamics of divine revelation. In this sense, God takes the initiative to reveal himself to mankind, and He wanted from his eternal silence to communicate his will and his Word. The Word is the expression of the exodus of God's revelation in dynamics. Word exodus and sustain hope and faith and nourish the believer in listening, in proclaiming and bearing witness. By revealing himself in history in Jesus Christ, God empowers the human heart in kerygmatica power to proclaim the Word. God is a Being of revelation and communication in itself. The novelty of God is within the Easter faith that streamlines and places the human being, loved and chosen, on the horizon of hope and the meeting of Christ. Openness to transcendence is a human reality that allows meeting the host of the ethical basis of the horizon as diverse meaning to life with their webs of relationships. Thus, the person is subject to ethical and sustainable ethics depending on your conscious opening another one in the same condition as subject.